2019
DOI: 10.1038/s41386-019-0312-0
|View full text |Cite
|
Sign up to set email alerts
|

Acute and long-term effects of electroconvulsive therapy on human dentate gyrus

Abstract: Electroconvulsive therapy (ECT) is the most effective treatment for severe depression, although the underlying mechanisms remain unclear. Animal studies have consistently shown that electroconvulsive stimulation induces neuroplastic changes in the dentate gyrus. To date, few studies have investigated the effect of ECT on human hippocampal subfields. In the current study, structural magnetic resonance imaging (MRI) was conducted in 25 patients with major depressive episodes at 3 time points: before ECT (TP1), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 50 publications
1
47
0
1
Order By: Relevance
“…To answer this first question, we collaborated with a group from Tokyo University. Together with Takamiya et al we reanalyzed their previously published data [5], now reporting a significant correlation between changes in DG volume and clinical response after bilateral ECT in an independent sample using 3 tesla MRI [6]. In the aforementioned previously published study [5], Takamiya et al reported volume changes in DG volumes but did not find a simple linear correlation between difference scores in DG volume and HAM-D.…”
Section: ) Whether This Observation Will Hold In Larger Samples mentioning
confidence: 94%
See 1 more Smart Citation
“…To answer this first question, we collaborated with a group from Tokyo University. Together with Takamiya et al we reanalyzed their previously published data [5], now reporting a significant correlation between changes in DG volume and clinical response after bilateral ECT in an independent sample using 3 tesla MRI [6]. In the aforementioned previously published study [5], Takamiya et al reported volume changes in DG volumes but did not find a simple linear correlation between difference scores in DG volume and HAM-D.…”
Section: ) Whether This Observation Will Hold In Larger Samples mentioning
confidence: 94%
“…Together with Takamiya et al we reanalyzed their previously published data [5], now reporting a significant correlation between changes in DG volume and clinical response after bilateral ECT in an independent sample using 3 tesla MRI [6]. In the aforementioned previously published study [5], Takamiya et al reported volume changes in DG volumes but did not find a simple linear correlation between difference scores in DG volume and HAM-D. However, when they implemented the same repeated measures correlation [7] we used in our study [2], a significant correlation was found between a decrease in HAM-D score and an increase in right DG volume (yet not significant in left DG [6]).…”
Section: ) Whether This Observation Will Hold In Larger Samples mentioning
confidence: 99%
“…However, a recent mega‐analysis did not find relationships between hippocampal volume enlargements observed post ECT and clinical response, suggesting enlargement is masked or at least in part driven by processes related to seizure therapy itself (Oltedal et al, ). At the same time, smaller sample size studies have found ECT‐induced volume increases in the hippocampal dentate gyrus to associate with treatment outcome specifically (Nuninga et al, ; Takamiya et al, ), and ECT response is shown to positively relate to greater structural connectivity between hippocampus and fronto‐limbic regions (Kubicki et al, ). Notably, though seemingly disparate, the above findings are in line with our results indicating that a more complex multimodal brain network, including the hippocampus and connected regions, underlies depressive symptom improvement at the brain systems level.…”
Section: Discussionmentioning
confidence: 99%
“…Das Risiko für Schlaganfälle ist durch eine EKT-Behandlung nicht erhöht, auch nicht nach vorangegangenem Schlaganfall (Rozing et al, 2019). EKT ruft keine nachweisbaren Hirnschädigungen hervor; bisherige Studien zeigen im Gegenteil sogar Hirnvolumenzunahmen in bestimmten Regionen (Nuninga et al, 2019;Sartorius et al, 2019;Takamiya et al, 2019;zwei Metaanalysen: Gbyl & Videbech, 2018;Takamiya et al, 2018). Es gibt keinen klaren Hinweis auf ein erhöhtes Risiko nach einer EKT an einer Epilepsie zu erkranken (Bøg et al, 2018).…”
Section: Unerwünschte Wirkungen Und Risiken Von Ektunclassified